Neither Demon nor Angel: Theology and Empirical Studies on Reciprocity - Maßmann, Alexander (Modern theology, 2021)
Anthropological theory on gift reciprocity has amounted to a fruitful contribution to theology, as different thinkers have portrayed God’s grace as an undeserved gift that nevertheless obliges the recipient to make a non-transactional return gift (John Milbank, John Barclay). Alternative views that highlight a radically unilateral understanding of the gift are sometimes dualistic (J. Louis Martyn, Philip Ziegler). This article connects the discourse on giving with the biological discussion of reciprocity, pursuing a realistic theology that is open to learning from the empirical sciences. In spite of abiding differences in non-human and human gift-giving, parallels between the two buttress a more robust view of creation than suggested by dualism. In addition, a third position, which affirms unilateral gratuity but not dualism (Kathryn Tanner), remains aloof of nature, showing tensions with human experience where it appeals to experience. However, this does not mean that theologians should embrace the model of gift reciprocity exclusively. While this conceptual scheme makes a lasting contribution to theology, more radical expressions of Paul’s theology of grace affirm an unconditional understanding of grace. Besides reciprocity, there are also facets in primate behavior that are in keeping with a unilateral practice of giving.